Adverse drug reaction reporting among physicians working in private and government hospitals in Kuwait - F.M. Alsaleh; J. Lemay; R.R. Al Dhafeeri; S. AlAjmi; E.A. Abahussain; T. Bayoud (Elsevier, 2017)
Introduction: To improve patient safety and care, the identification and reporting of adverse drug reactions (ADRs) should be systematic and mandatory for all healthcare professionals (HCPs). Physicians remain the main HCPs with direct patient care whose role in ADRs reporting should not be ignored. Objective: To document the awareness and attitude of physicians working in private and government hospitals in Kuwait with regard to pharmacovigilance (PV) and ADR reporting and to identify their practices of reporting ADRs. Material and methods: A cross-sectional study was conducted using a paper-based 25-item questionnaire. The Statistical Package for Social Science (SPSS) was used for data analysis. Results: A total of 1017 questionnaires were distributed to the eligible physicians in the government and private hospitals, giving a response rate of 84.2% and 83.0%, respectively (an overall response rate of 83.8%). Private physicians exhibited a better knowledge profile with regards to the purpose of PV (75.2% vs 64.8%; p = 0.002) and the correct ADR definition (75.8% vs 65.3%; p = 0.001). The majority of physicians showed good attitude towards reporting ADRs, nevertheless, private physicians had a significantly stronger belief that reporting ADRs is a professional obligation (93.4% vs 85.5%; p = 0.001). Three quarters of the study population (74.6%) had identified an ADR during their daily practice, however, only a small proportion (34.2%) confirms having ever reported ADRs. Regardless, significantly more private physicians had done so (42.4% vs 29.6%; p < 0.001). ADR reporting was significantly higher in physicians who knew the correct ADRs to be reported (adjusted OR = 1.86, p = 0.036), and those who were aware of any center or ADR reporting system in Kuwait (adjusted OR = 2.88, p = 0.020). Conclusions: A national PV center empowered by clear legislation on "how" and "what" to report should improve physicians' reporting practices and hence is required in the country. This should be combined with constant training and education in this regard. Keywords: Pharmacovigilance, Adverse drug reactions, Physicians, Hospitals, Private, Government